Philanthropy and the National Park Service - Vaughn, J. author. aut Link
XIV, 213 p.
Keywords: As the National Park Service prepares for its 2016 centennial, this book provides an in-depth analysis of the role of philanthropy and the national parks - exploring the challenges faced when working with non-profit philanthropic partners.